INNOVATION OF ISLAMIC BANKING INDUSTRY AS AN ALTERNATIVE ISLAMIC ECONOMIC DEVELOPMENT IN INDONESIA - FITHRIAH, NURHANI (Jurnal Jurisprudence, 2017)
One of potential exploration and manifestation of the communitys contribution to the national economy, is the development of an economic system based on the value of Islamic (Sharia) by lifting its principles into the National Legal System. Shariah principles based on the values of fairness, expediency, balance, and universality (rahmatan lil alamin). Those values are applied in banking regulation that is based on the so-called Sharia Islamic Banking. Principles of Islamic Banking is part of Islamic teachings related to the economy. In addition, to provide assurance to the people who still doubt shariah Islamic Banking operations during this time also set of business activities that do not conflict with Sharia Principles include business activities that do not contain elements of riba, maisir gharar, haram, and zalim. A separate regulation for Islamic Banking is an urgent thing to do, to ensure compliance with Shariah principles, the principles of the Bank for Islamic Bank, and no less important is expected to mobilize funds from other countries that requires the regulation of the Islamic Bank. Problems faced, how the strategy and the constraints faced in Islamic Banking Industry Product Innovation in developing the economy in Indonesia by Islamic Banking Act. This study aims to look for and find in the practice of the ways and forms of Islamic banking product innovation, as well as the constraints that it faces.This research, analytical, descriptive and normative juridical approach, and aims to provide a complete picture of the facts and the systematic application of Sharing in Islamic banks. Furthermore, the data were analyzed through statutory provisions in force, which among one another should not be contradictory, pay attention to the hierarchy with the aim to achieve legal certainty, by searching and digging law who live in the community, whether it is written or unwritten (Islamic law).The results showed that the strategy which remove products of Islamic banking industry innovation, improve human resources SDI), and marketing of products strategically. Constraints faced in Islamic Banking Industry Product Innovation in developing the economy in Indonesia, it is very difficult to do because fixated on Islamic principles. Suggestions put forward, should disseminate innovative products to the public and the effectiveness of supervision of Islamic banks (Internal & ekstenal).